KONTRIBUSI METODE NEURO-LINGUISTIC PROGRAMMING PADA KONSENTRASI PELARI CEPAT (SPRINTER) - Miftakhul Jannah (Universitas Negeri Surabaya, 2010)
This research was designed to test the contribution Neuro-Linguistic Programming to sprinters concentration. There are sixteen sprinters from Training Center Local of East Java participated in this research. Data were analyzed using difference mean pretest and posttest concentration score. The result obtained indicates that : (1) mean pretest concentratrion score = 7,25. (2) mean posttest concentratrion score = 10,125. (3) Mean gain score = 2,9375. There was difference sprinters concentration between before and after received Neuro-Linguistic Programming (NLP) Training. After received NLP Training sprinters concentration were increased. Sprinterss concentration increase through the NLP training because of subjects readiness and participation, training method and training items, with they are interrelated to each other.